Big Brother Mentoring in the Let’s Teach for Hungary Program - Godó, Katalin (Central European Journal of Educational Research, 2021)
The number of mentoring programs within the framework of schools is increasing both internationally and domestically (Raufelder & Ittel, 2012; Fejes et. al., 2009). Besides traditional mentoring, the role of peer mentoring (Miller, 2002) has also come to the fore in recent years. In our study, we focus on cross-age peer mentoring (Miller, 2002; Sipe, 2005), where older youth mentor younger youth. One example of this in Hungary is the Let’s Teach for Hungary (LTHMP) mentoring program, where undergraduate students mentor primary school students. In our research, we studied mentors at the University of Debrecen who had completed at least two semester-long cycles in the program. We were curious about how the COVID-19 pandemic period affected mentoring, so we examined the transition of a mentoring program based on a personal meeting to online mentoring, and its pivotal points, advantages, and disadvantages. As a method, we used qualitative interview analysis, during which we worked with semi-structured interviews, recorded in the spring of 2020 and 2021 – during the global pandemic situation – with a total of 50 mentors. The content analysis of the interview texts was performed based on the codes formulated based on the theory, and the emic codes emerged in the interviews (Creswell, 2012). Our results show that mentors can be grouped into different types based on their attitudes towards online mentoring. Overall, the digital transition has been a big challenge. The biggest problem was the lack of equipment. The issue of age has been also an important factor in terms of the sense of digital comfort. We noticed the phenomenon of Big Brother Mentoring and the importance of chameleon mentors. Our research, which can fill a gap, highlights both the challenges and benefits of online mentoring. In addition, we can also contribute to the effective and successful operation of the Let’s Teach for Hungary Mentoring Program.